Jambu production (Acmella oleracea [(L.) R. K. Jansen]) using different organic fertilizers at planting and as top dressing - Alves, Thatiane Nepomuceno [UNESP]; Inácio Cardoso, Antonio Ismael [UNESP]; de Carvalho, Joseantonio Ribeiro [UNESP]; Nordi, Nicholas Taborda [UNESP]; de Oliveira, Marcelo Munhoz Venâncio; Slusarz da Silva, Irene Santos [UNESP]; Pereira Guedes, Politon Thiago [UNESP] (Lepidus Tecnologia, 2023)
The aim of this study was to evaluate the effect of different forms of application (before planting and as top dressing) of organic fertilizers, namely castor bean cake and hoof and horn powder, on the production of jambu plants. The experiments were conducted at the Experimental Farm of São Manuel, SP, and at the ‘Estância Três Nascentes’ site in Botucatu, SP. Seven treatments were evaluated in a 2 x 3 + 1 factorial design, with two organic fertilizers, castor bean cake (CBC) and hoof and horn powder (HHP), and three forms of application (100% before planting, 100% as top dressing, and 50% before planting + 50% as top dressing), plus a control treatment. The experimental design was a randomized complete block with four replications. Plant height, number of inflorescences (NI), fresh weight of inflorescences (FWI), fresh weight of vegetative parts (FWVP), and total fresh weight (TFW) were evaluated at each location. In São Manuel, there was a difference between fertilizers in the forms of application, 100% before planting and 50% before planting + 50% as top dressing, for FWVP and for TFW only in the first form. In Botucatu, HHP resulted in higher NI when applied 100% before planting and FWVP and TFW between fertilizers when applied 100% as top dressing. The increases compared to the control, with HHP and CBC, were 81%, 83%, 168%, 83%, and 95% in São Manuel and 19%, 42%, 316%, 56%, and 67%, in Botucatu, for plant height, NI, FWI, FWVP, and TFW, respectively, confirming the importance of supplementing base fertilization with organic compounds.
Keywords: castor bean cake; fresh weight; hoof and horn powder; inflorescences; nitrogen